Impact of the Atatürk Dam on the propagation of meteorological drought in Şanlıurfa province - Keskiner, Ali Demir; Yücel, Tuba; Tuylu, Gökhan İsmail; Şimşek, Mehmet (My University, 2024)
Global warming is considered one of the most significant causes of climate change. The increase in the frequency and severity of natural disasters such as floods, droughts, etc. in recent years is evaluated as a sign of climate change. In this context, the study conducted in Şanlıurfa province, which has a surface area of 19.242 km², aimed to determine the spatial and temporal propagation of meteorological drought in two different periods using the De Martonne (IDM), De Martonne-Gottman (IDMG) and Erinç (Im) methods. Long-term monthly total precipitation (mm), average temperature (?C) and average maximum temperature (?C) series obtained from 12 meteorological observation stations located within and outside the provincial borders were used as source material. The annual drought index values were calculated for each station using three methods. Missing years in the calculated drought index series were completed by correlation and regression analysis. Taking the year 1991, when the Atatürk Dam started to hold water, as the starting year of the 2nd period, the series of stations were divided into 2 different time scales: the 1st period (1961-1990) and the 2nd period (1991-2020). Using the median values of the drought index series representing the stations, IDM, IDMG and Im “Annual Climate Class Maps” of Şanlıurfa were produced for 2 different periods with a resolution of 200x200 m by the Inverse Distance Method. Consequently, the spatial and temporal propagation of meteorological drought in Şanlıurfa province according to IDM, IDMG and Im methods is from south to north, the severity of drought increases in period 2, the Atatürk Dam could not prevent the propagation of drought and there is no significant difference between the methods in terms of determining drought propagation. If global warming continues at the current rate until the end of this century, Akçakale, Ceylanpınar and Viranşehir have been identified as priority drought-affected areas and are likely to experience severe droughts and face desertification.
Keywords: Desertification; Climate classification; De Martonne; De Martonne- Gottman; Erinc